2019
DOI: 10.18280/rcma.290206
|View full text |Cite
|
Sign up to set email alerts
|

Split-Hopkinson Pressure Bar Test and Numerical Simulation of Steel Fiber-reinforced High-strength Concrete

et al.

Abstract: The fabrication and optimization of the shelter layer are critical to the performance of the protective works. The novel shelter layer made of steel fiber-reinforced high-strength concrete (SFRHSC) is much more advantageous than that of ordinary concrete. This paper carries out a split-Hopkinson pressure bar (SHPB) test on the steel fiber and high-strength concrete, two main components of the SFRHSC, aiming to disclose the failure features and dynamic compressive strength of the SFRHSC under dynamic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The fabrication and optimization of the occupancy layer is very important for the performance of protective work. The new protective layer made of high quality concrete reinforced by steel fibers (SFRHSC) is far more profitable than ordinary concrete [12].…”
Section: Figure 2 Types Of Fibermentioning
confidence: 99%
“…The fabrication and optimization of the occupancy layer is very important for the performance of protective work. The new protective layer made of high quality concrete reinforced by steel fibers (SFRHSC) is far more profitable than ordinary concrete [12].…”
Section: Figure 2 Types Of Fibermentioning
confidence: 99%
“…Dalvand et al [32] used zeolite material to partially replace ordinary silicate cement, which could effectively enhance the bond strength in the interfacial transition zone between fine aggregate and cement paste, thus improving the toughness and postpeak behavior. In recent years, a number of researchers have studied the mechanical properties of rapid-hardening HSFRC under quasi-static loading; however, there is limited research on its dynamic mechanical properties under impact loading [29,33]. Previous studies have shown that rapid-hardening HSFRC has good dynamic mechanical properties and its use in repairing bridge deck pavement allows a structure to dissipate more energy at the material level, reduce amplitude and stress, and improve the overall structural damping [33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of researchers have studied the mechanical properties of rapid-hardening HSFRC under quasi-static loading; however, there is limited research on its dynamic mechanical properties under impact loading [29,33]. Previous studies have shown that rapid-hardening HSFRC has good dynamic mechanical properties and its use in repairing bridge deck pavement allows a structure to dissipate more energy at the material level, reduce amplitude and stress, and improve the overall structural damping [33].…”
Section: Introductionmentioning
confidence: 99%